Hubungan Antara Kecerdasan Spiritual Dengan Burn Out Pada Perawat Di RSUD R. Syamsudin, SH Sukabumi Jawa Barat - Mr. Usman (Jurnal Psikologi, 2005)
Being a nurse is easily to burn out since his or her job is stressful. One is more like likely to burn out when his or her spiritual quotient is low. Forty nurses participate in this research. The spiritual quotient scale is designed through 47 items and 7 aspects i.e. self conscious, visionary, flexible, having holistic opinion, able to change him or herself firstly and then modify others, being an inspiration resource for others, and able to self reflect. The burn out scale is also designed through 32 items and 3 aspects i.e. emotional exhausted, inferior feeling, and depersonalization. The Pearson correlation between the spiritual quotient variable and the burn out scale indicates that r = -0.678 with p<0.000. It shows that the higher spiritual quotient the lower probability he or she suffers burn out. The determinant coefficient is on moderate level (0.459). It means that the prediction of burn out variable by the spiritual quotient is only 45.9%. Other variables which do not include on this research contribute 54.1% on explaining the emerging of burn out. It may be those subjects (95%) are still living with their parents. That kind of living arrangement is more likely to eliminate the burn out case.